Case report: pulmonary lymphoepithelial carcinoma mimicking tuberculosis - Senlin Zhan; Changyin Feng; Kaihua Pang; Hongjuan Qin; Peize Zhang (BMC Pulmonary Medicine)
Abstract Pulmonary lymphoepithelial carcinoma (PLELC) is distinct subtype of primary lung cancer, closely associated with Epstein-Barr virus (EBV) infection. Histopathological features sometimes mimic granulomatous inflammation. We present the case of a woman who was doubted with pulmonary and lymph node tuberculosis based on a pathological demonstration of granulomatous inflammation. A final diagnosis of PLELC was made after lung biopsy and EBV tests. Given the complex and rarely seen of the disease, further studies are needed to investigate the clinical and pathological manifestations in patients with PLELC. Clinical trial number: Not applicable.